The diagnostic accuracy of PIK3CA mutations by circulating tumor DNA in breast cancer: an individual patient data meta-analysis. (September 2022) - Galvano, Antonio; Castellana, Luisa; Gristina, Valerio; La Mantia, Maria; Insalaco, Lavinia; Barraco, Nadia; Perez, Alessandro; Cutaia, Sofia; Calò, Valentina; Bazan Russo, Tancredi Didier; Francini, Edoardo; Incorvaia, Lorena; et al.
Background: The circulating tumor DNA (ctDNA) diagnostic accuracy for detecting phosphatidylinositol 4, 5-bisphosphate 3-kinase catalytic subunit alpha ( PIK3CA ) mutations in breast cancer (BC) is under discussion. We aimed to compare plasma and tissue PIK3CA alterations, encompassing factors that could affect the results. Methods: Two reviewers selected studies from different databases until December 2020. We considered BC patients with matched tumor tissue and plasma ctDNA. We performed meta-regression and subgroup analyses to explore sources of heterogeneity concerning tumor burden, diagnostic technique, sample size, sampling time, biological subtype, and hotspot mutation. Pooled sensitivity, specificity, positive likelihood ratio (PLR), negative likelihood ratio (NLR), diagnostic odds ratio (DOR), and the related area under the curve (AUC) were elaborated for the overall population and each subgroup. Results: The pooled analysis was carried out on 25 cohorts for a total of 1966 patients. The overall ctDNA sensitivity and specificity were 0.73 (95% CI: 0.70–0.77) and 0.87 (95% CI: 0.85–0.89). The AUC was 0.93. Pooled concordance, negative predictive value and positive predictive value values were 0.87 (95% CI: 0.82–0.92), 0.86 (95% CI: 0.81–0.90), and 0.89 (95% CI: 0.81–0.95) with pooled PLR, NLR, and DOR of 7.94 (95% CI: 4.90–12.86), 0.33 (95% CI: 0.25–0.45), and 33.41 (95% CI: 17.23–64.79), respectively. The pooled results consistently favored next-generation sequencing (NGS)- over polymerase chain reaction-based methodologies. The best ctDNA performance in terms of sensitivity, specificity, and AUC (0.85, 0.99, and 0.94, respectively) was observed in the low-time sampling subgroup (⩽18 days between tissue and plasma collection). Meta-regression and subgroup analyses highlighted sampling time as a possible major cause of heterogeneity. Conclusions: These findings reliably estimate the high ctDNA accuracy for the detection of PIK3CA mutations. A ctDNA-first approach for the assessment of PIK3CA mutational status by NGS may accurately replace tissue tumor sampling, representing the preferable strategy at diagnosis of metastatic BC in patients who present with visceral involvement and at least two metastatic lesions, primarily given low clinical compliance or inaccessible metastatic sites.